Reactivities of silaimines with boranes: from cooperative B-H bond activation to donor stabilized silyl cation - Bisai, Milan Kumar; Sharma, Vishal; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
The recently published silylene with a tris(trimethylsilyl) group, PhC(NtBu)(2)SiSi(SiMe3)(3) (1), was reacted with the organic azides such as SiMe3N3 and AdN(3) to form the respective hypersilylsilaimines, PhC(NtBu)(2)Si(=NR)Si(SiMe3)(3) 2 (R = SiMe3) and 3 (R = Ad). The B-H bond of HBpin or HBcat was split across the Si=N bond upon reaction with 2, which generated 4 and 5, respectively. However, we could not obtain the crystals of 4 and 5 appropriate for X-ray diffraction. Subsequently, we performed the analogous reactions with a related silaimine PhC(NtBu)(2)Si(=NSiMe3)N(SiMe3) 2 (2') and isolated similar B-H bond activated products 6 and 7. The reaction of 2' with HBCl2 resulted in donor stabilized silyl cations (8 and 9) supported by an amidinate ligand.